2018
DOI: 10.1016/j.actbio.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation of model drug carriers enhances phagocytosis by primary human neutrophils

Abstract: The work in this manuscript is highly significant to the field of drug delivery, as it explores in-depth the effects of polyethylene glycol (PEG) coatings, which are frequently used to prevent phagocytic clearance of particulate drug carriers, on the phagocytosis of such carriers by neutrophils, the most abundant leukocyte in blood circulation. Surprisingly, we find that PEGylation enhances uptake by primary human neutrophils, specifically in the presence of human plasma. This result suggests that PEGylation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 58 publications
2
59
0
Order By: Relevance
“…Some investigations support the inverse correlation between particle size and neutrophil uptake. Kelley et al [29] demonstrated the increased human neutrophil uptake following the size reduction of polystyrene nanoparticles. Gifford et al [30] suggested a facile uptake of iron oxide nanoparticles with a mean diameter of 110 nm by leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations support the inverse correlation between particle size and neutrophil uptake. Kelley et al [29] demonstrated the increased human neutrophil uptake following the size reduction of polystyrene nanoparticles. Gifford et al [30] suggested a facile uptake of iron oxide nanoparticles with a mean diameter of 110 nm by leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of poly(ethylene glycol) (PEG) onto the surface of nanoparticles is commonly thought to prevent particle opsonization and macrophage uptake. However, a recent study suggested, instead, that neutrophils preferentially internalized PEGylated particles (i.e., polystyrene microspheres) in the presence of human plasma 20 . Notably, when the authors used model cell lines such as HL-60 or THP-1 cultured in standard cell medium supplemented with 10% fetal bovine serum, PEGylation reduced uptake of the particles.…”
Section: Nanomaterials Effects On Neutrophilsmentioning
confidence: 97%
“…Furthermore, low PEG densities on nanoparticles resulted in rapid clearance of nanoparticles. Another study found that the addition of PEG to the surface of PS-COOH nanoparticle increased their uptake by neutrophils across multiple particles sizes of 2 µm, 500 nm, and 200 nm [24]. These studies also found no significant difference between the internalization of 200 nm PS-COOH nanoparticles [8].…”
Section: Discussionmentioning
confidence: 93%